Effect of Thammasat Weight Reduction Program on Weight Loss and Quality of Life - จิตวโรภาส รุ่งรัตน์; อยู่คง วิไล; เวชชสัสถ์ ตรีทิพย์; บุรวัฒน เบญจพรรณ; ทองลิ่ม จุฑามาศ; ชาวนา กัลยาณี; รักไทย นาฏตยา; เซ็นน้อย นฤทธิ์; ภูมิภาค นารถวดี; สังข์ศิริ สุธีรา; สุเชาว์อินทร์ กนกนันทร์; ธาระวานิช ทิพาพร (Journal of Health Science of Thailand, 2020)
This study aimed to assess the effectiveness of Thammasat weight reduction program in weight loss and quality of life in overweight or obese participants. Thammasat weight reduction program is an integrated activity by multidisciplinary personnel focusing on comprehensive mind management with positive psychology and coaching along with diet control, physical activity and exercise training. The five in-session workshops were organized for every 2-3 months in a total of 9 months duration. Physical examinations were performed in every workshop. Quality of life was evaluated by using the World Health Organization Quality of Life Brief–Thai version (WHOQOL-BREF-THAI) and blood chemistry tests were obtained before and after attending Thammasat weight reduction program. Analysis of the data involved both descriptive and inferential statistics. The findings were compared by paired sample T-Test. Eighteen persons participated in this research. The mean age of the participants was 44.8±11.6years. Fourteen participants (77.8%) were females. Average initial body weight (BW) and body mass index (BMI) were 78.3±16.3 kg and 30.4±5.6 kg/m2 , respectively. At the end of the study, participants showed significant reduction in BW and BMI (-2.2±3.3 kg, p<0.05 and -0.8±1.3 kg/m2 , p<0.05, respectively). At least a 5% weight reduction was accomplished by 33.3% of participants. No significant change in triglyceride and HDL-cholesterol from baseline after attending this program. Total cholesterol, LDL-cholesterol and fasting blood glucose were significantly increased (+21.2±30.1 mg/ dl, p<0.05; +23.1±31.8 mg/dl, p<0.05 and +7.5±6.1 mg/dl, p<0.01, respectively), however LDL-cholestorol/HDL ratio was not significantly changed. Overall quality of life was significantly improved from fair to good level (+8.4±6.6, p<0.01). In conclusion, a short-term Thammasat weight reduction program leads to significant weight losses along with improved the overall quality of life in overweight/obese subjects.